The planet remade : how geoengineering could change the world - Morton, Oliver (Princeton University Press, 2016)
In an effort to rethink our responses to the crisis of global warming, a small but increasingly influential group of scientists is exploring proposals for planned human intervention in the climate system: a stratospheric veil against the sun, the cultivation of photosynthetic plankton, fleets of unmanned ships seeding the clouds--all technologies of the new field of "geoengineering." In The planet remade, journalist Oliver Morton explores the history, politics, and cutting-edge science of this new field, weighing both the promises and perils of its controversial strategies and examining its scale and ambition relative to the profound changes in the planet's clouds, soils, winds, and seas during the last century.--Adapted from publisher description.